Circular Economic Model of Waste Bank Based on Technological Innovation : A Comprehensive Bibliometric Insight - Rully Yusuf; Raldi Hendro Koester (International Journal of Environmental, Sustainability and Social Science, 2026)
The circular economy contributes to increasing environmental resilience and the social welfare of society. This analysis aims to identify the development of an effective waste bank circular economy model through technological innovation. The method used is bibliometric analysis with VOSviewer software. The research results show that the main challenges faced are a lack of infrastructure, public awareness, and inadequate regulations in several countries. However, this research also highlights the enormous opportunities offered by circular economy models, such as the creation of new jobs, reduced dependence on non-renewable resources, and increased global competitiveness. The implications of implementing a circular economy model for sustainable development support increased resource utilization efficiency, new job creation, and strengthened economic resilience. The implementation of circular economy models in China, Germany, Australia, and Indonesia demonstrates distinct advantages and challenges. China focuses on recycling with subsidies, but still faces challenges in law enforcement and infrastructure. Germany has succeeded in recycling waste with renewable energy, but focuses more on technological innovation than on social innovation.